A novel filler of biocomposites for long-term self-regulated delivery of immunomodulatory and antibacterial components to accelerate bone regeneration. (1st June 2022) - Min, He; Li, Kaide; Wang, Qian; Gao, Xinghui; Xie, Li; Tian, Weidong
Abstract: Undesirable immune response and bacterial infection still remain critical challenges for the applications of biodegradable scaffolds. Herein, we assembled tannic acid (TA)/Zn 2+ based metal-phenolic network complexes (MPNs) as a novel filler to render the scaffold with immunomodulatory and antibacterial functions. Besides the unique characteristics of combining the advanced functions of both TA (immunomodulation) and Zn 2+ (antibacteria), another prominent feature of the filler was that it allowed to release its components in a sustainable constant rate manner, without initial burst release, lasting for more than 30 days, due to the supramolecular network structures and dynamic coordination bonds. Consequently, the modified scaffold could not only control the initial severe acute inflammation to a moderate level, but also displayed a full-course inhibition on later biodegradation-induced chronic inflammation. The manipulated anti-inflammatory micro-environment was more beneficial for in vivo osteogenesis. Additionally, the constant release rate of Zn 2+ rendered the scaffold stable and long-term antibacterial performance, meanwhile avoiding cytotoxicity of Zn 2+ . As an emerging class of multi-functional metal-organic materials with a high degree of function modularity in terms of the choice of different metal ions and phenolic ligands, this work paved a new path for the applications of MPNs to advance multi-functional biocomposites. Graphical abstract: Image 1 Highlights: A pioneering work of exploring a novel type of filler for advanced biocomposites. MPNs based filler achieved self-regulated sustained release of its bioactive compounds. Long-term immunomodulatory and antibacterial functions were obtained after modified by the filler.